Current Trends in Semantic Web Technologies: Theory and Practice - Alor-Hernández, Giner; Sánchez-Cervantes, José Luis.; Rodríguez-González, Alejandro; Valencia-García, Rafael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents innovative and high-quality research regarding the implementation of Semantic Web technologies for knowledge representation and developing intelligent applications in various domains. Semantic Web technologies have inspired many people to create innovative technologies and applications for knowledge representation, Semantic Searches, NLP and Social Networks. The goal of this book is to collect and consolidate novel and high-quality research contributions on Semantic Web technologies and their theoretical and practical application to a range of different domains. In addition to researchers, the book offers a valuable resource for PhD students, master and undergraduate students in IT-related fields such as Computer Science and Information Systems. .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence